Electrospinning/Electrospray of Ferrocene Containing Copolymers to Fabricate ROS-Responsive Particles and Fibers - Lee, Hoik (Polymers (Basel), 2020)
We demonstrate an electrospray/electrospinning process to fabricate stimuli-responsive nanofibers or particles that can be utilized as stimuli-responsive drug-loaded materials. A series of random copolymers consisting of hydrophobic ferrocene monomers and hydrophilic carboxyl groups, namely poly(ferrocenylmethyl methacrylate-r-methacrylic acid) [poly(FMMA-r-MA)] with varied composition, was synthesized with free radical copolymerization. The morphologies of the resulting objects created by electrospray/electrospinning of the poly(FMMA-r-MA) solutions were effectively varied from particulate to fibrous structures by control of the composition, suggesting that the morphology of electrosprayed/electrospun copolymer objects was governed by its composition and hence, interaction with the solvent, highlighting the significance of the balance of hydrophilicity/hydrophobicity of the copolymer chain to the assembled structure. Resulting particles and nanofibers exhibited largely preserved responsiveness to reactive oxygen species (ROS) during the deposition process, opening up the potential to fabricate ROS-sensitive material with various desirable structures toward different applications.